Designing social behaviour change in households: sustainable mobility intervention and follow-up study - Saga Sofia Santala; Saga Sofia Santala; Merja Honkanen; Michael Lettenmeier; Michael Lettenmeier; Michael Lettenmeier; Jari Kolehmainen; Salla Lahtinen (Frontiers in Sustainability)
Limiting global warming to 1.5 degrees requires consistent action by people to change their lifestyles in order to limit annual household-related carbon emissions to 2.5 tonnes per person by 2030. As the required mobility reduction measures have already been identified, the challenge remains in scaling up the changes into a mainstream practice. Our study explored whether the involvement of close social communities, especially households, in the change process could be effective in achieving the required measures. Through a Climate Puzzle game intervention and a six-month follow-up study with 12 households in Espoo, Finland, we investigated the role of close social communities in implementing the planned sustainable mobility behaviour change. The findings are presented through 12 household narratives. These narratives show that the adoption of new sustainable mobility behaviours is influenced by both (infra)structural and social relationship factors and that close social communities can hinder or facilitate the shift of everyday mobility behaviours towards being more sustainable in diverse ways. The findings suggest that design interventions should target larger social communities rather than just individuals in order to achieve the 2.5 tonne target. The study also indicates that socially tailored interventions and low-carbon solutions should be developed and targeted at city districts to help households create and maintain lifestyle changes.